Legal sources Advocacy (Journal of actual problems of jurisprudence, 2018)
This article analyzes the legal acts of government bodies containing norms, regulating activity of advocacy. Law sources of law are normative legal acts regulating law-legal relationship, and their problems. And the way the solution to this problem.Key words: the lawyer, lawyer activity, regulations, the criminal proceedings.